2014
DOI: 10.11607/jomi.3173
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of the Pterygomaxillary Area for Implant Placement: Cone Beam Computed Tomographic Scanning in 100 Patients

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…25 , the height of the pterygopalatine suture has been reported to be 13.1 mm, which is in concordance with the measurement in our study, 12.5 mm (SD 1.8 mm). Studies have suggested that implants measuring 13.0 to 18.0 mm could be appropriated to ensure an engagement in the cortical bone of the pterygoid process 17,26 .…”
Section: Discussionmentioning
confidence: 99%
“…25 , the height of the pterygopalatine suture has been reported to be 13.1 mm, which is in concordance with the measurement in our study, 12.5 mm (SD 1.8 mm). Studies have suggested that implants measuring 13.0 to 18.0 mm could be appropriated to ensure an engagement in the cortical bone of the pterygoid process 17,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were: English and Spanish language; studies in humans; studies reporting implants in the pterygoid, pterygomaxillary, or maxillary tuberosity regions; studies with at least 1 year of follow-up; clinical cases with a minimum of 10 patients; randomized controlled trials (RCTs) and prospective studies; retrospective and prospective studies. The following definition of pterygoid implant was considered: an implant inserted through the maxillary tuberosity, engaging with the dense cortical bone formed by the pyramidal process of the palatine bone and the pterygoid laminae of the sphenoid bone 8,9,19 ; implant length of minimum 13 mm and able to effectively reach the pterygoid plate 6,10,11,13 . The key words: "pterygoid implants," "pterygomaxillary implants," "pterygoid plate implants," and "tuberosity implants".…”
Section: Methodsmentioning
confidence: 99%
“…Bone graft procedures, such as maxillary sinus lifting and onlay/inlay grafts, have also been used to address insufficient bone volume in this region [6][7][8][9][10] . There are few studies in the literature evaluating pterygoid implant survival rates in short and long term follow-up studies [11][12][13] . Although a definition of pterygoid implants is provided in the glossary of Oral and Maxillofacial Implants (GOMI), as an "implant placed through the maxillary tuberosity and into the pterygoid plate", several studies in the literature have incorrectly included implants inserted into the tuberosity or the pterygomaxillary region as pterygoid implants 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Several muscles attach to or operate via, the maxillary tuberosity and the pterygoid process of the sphenoid bone, including the buccinator, the pterygoid muscles, levator veli palatini (levator palati), and tensor veli palatine (tensor palati) [32]. Likewise, the pterygoid hamulus mimics Archimedean mechanical systems, having a pulley-like structure for the tensor palati, while the hamulus itself anchors a critical mechanical structure, the pterygomandibular raphe (pterygomandibular ligament) [32,33]. Besides, several notable neurovascular structures exist in the vicinity of the pterygoid process, primarily the mandibular branch of the trigeminal nerve, the middle meningeal artery, nervus spinosus, the petrosal nerves, as well as the neurovascular elements of the vidian canal [32,33].…”
Section: K-means and Hierarchical Cluster Analysismentioning
confidence: 99%
“…Likewise, the pterygoid hamulus mimics Archimedean mechanical systems, having a pulley-like structure for the tensor palati, while the hamulus itself anchors a critical mechanical structure, the pterygomandibular raphe (pterygomandibular ligament) [32,33]. Besides, several notable neurovascular structures exist in the vicinity of the pterygoid process, primarily the mandibular branch of the trigeminal nerve, the middle meningeal artery, nervus spinosus, the petrosal nerves, as well as the neurovascular elements of the vidian canal [32,33]. Accordingly, the current study is of prime importance for medicine, surgery, and biomimetics.…”
Section: K-means and Hierarchical Cluster Analysismentioning
confidence: 99%